Hybrid selection as a method of increasing mapping power for radiation hybrids. - Jones, H B (Genome Research, 1996)
Radiation hybrids have become a widely used tool for physical mapping. A drawback of the technique is that large numbers of hybrids are required to construct robust, high-resolution maps. The information contained within a panel of radiation hybrids is limited by the frequency of retention of chromosomal fragments from the donor cell line. In almost all experiments to date, the retention frequency has been below the optimal level; therefore, many hybrids are needed to produce high-quality maps. Because of the labor-intensive nature of large-scale mapping projects, it is important to make panels as small as possible. One method that has been adopted is to produce initially a large number of hybrids that are all typed with a few loci. Those hybrids showing satisfactorily high retention are admitted to the final panel and the rest are discarded. In this way, a panel of radiation hybrids with higher than expected retention can be created. Methods for conducting such a selection regime are discussed. To investigate the potential advantages of selecting hybrids based on their retention frequency, simulations were run under a variety of conditions. As expected panels with high retention (40%) provided better mapping resources than panels with lower (20%) retention. Beginning with an initial panel of 200 hybrids, comparisons of a random sample of 100 hybrids and the set of those 100 hybrids showing the highest marker retention demonstrated that selection may not be always the best strategy despite the increase in mean retention it yields. The selection of hybrids containing large numbers of fragments leads to an overestimation of the frequency of radiation-induced breaks. When breaks occur with high frequency (for example, when high radiation doses are used), the selection of hybrids leads to a loss of linkage and hence an inability to order the markers. As such, the merits of screening hybrids depends on both the radiation dose and the desired map resolution.